2015
DOI: 10.1093/aob/mcv130
|View full text |Cite
|
Sign up to set email alerts
|

Genetic assimilation: a review of its potential proximate causes and evolutionary consequences

Abstract: Identifying and characterizing the proximate mechanisms involved in phenotypic plasticity and genetic assimilation promises to help advance our basic understanding of evolutionary innovation and diversification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
175
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 170 publications
(186 citation statements)
references
References 147 publications
8
175
0
3
Order By: Relevance
“…Perturbation of Hsp90 was thus thought to uncover cryptic polymorphisms that do not typically show effects, thereby expanding the amount of heritable phenotypic variation in a population [1,2,47] (Fig 1A). Because of its role in buffering, Hsp90 began to be regarded as a capacitor that facilitates the accumulation of cryptic genetic variation [13,812]. …”
Section: Perturbation Of Hsp90 Impacts Heritable Phenotypic Variationmentioning
confidence: 99%
“…Perturbation of Hsp90 was thus thought to uncover cryptic polymorphisms that do not typically show effects, thereby expanding the amount of heritable phenotypic variation in a population [1,2,47] (Fig 1A). Because of its role in buffering, Hsp90 began to be regarded as a capacitor that facilitates the accumulation of cryptic genetic variation [13,812]. …”
Section: Perturbation Of Hsp90 Impacts Heritable Phenotypic Variationmentioning
confidence: 99%
“…However, recent theoretical modeling and experimental research has revealed that under the right conditions, environmentally induced plasticity can promote diversification and speciation events, such as in adaptive radiations (Ehrenreich & Pfennig 2016; Ghalambor et al 2007; Pfennig & McGee 2010; Wund et al 2008; Schneider & Meyer 2017). This could be accomplished in several ways, some of which include allowing the immediate exploitation of different niches in a novel environment, producing a rapid response to selection pressures in one generation, and enabling the repeated evolution of traits suited to different environments (Pfennig et al 2010; Yeh & Price 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This diversity of targets is important because it can both F I G U R E 1 An example of a novel, complex phenotype that appears to have evolved via plasticity-led evolution. Thus, a pre-existing developmental bias might have also played a role in the evolution of the distinctive carnivore morph [Color figure can be viewed at wileyonlinelibrary.com] LEVIS AND PFENNIG reduce the number of mutational steps required to evolve new regulatory connections (Abouheif & Wray, 2002;Ehrenreich & Pfennig, 2016;Kirschner & Gerhart, 1998;Pfennig & Ehrenreich, 2014) and provide numerous opportunities for the environment to influence development. Normally, Spea tadpoles develop into an "omnivore" morph (left), but if they eat large animal prey, such as shrimp (middle), they produce a distinctive "carnivore" morph (right), which is characterized by large jaw muscles, notched mouthparts (upper inset) and a short gut (lower inset).…”
Section: Flexible Regulationmentioning
confidence: 99%
“…Regarding this first step, the number and diversity of connections that can be rewired to generate new phenotypic outcomes is often large and therefore offers ample opportunities for environmentally contingent changes to occur. Of course, most traits are governed by numerous genetic variants (Mackay, Stone, & Ayroles, 2009), and these variants often show nonadditive effects because of their network structure (Ehrenreich & Pfennig, 2016;Gjuvsland, Hayes, Omholt, & Carlborg, 2007;Nuzhdin, Friesen, & McIntyre, 2012;Omholt, Plahte, Oyehaug, & Xiang, 2000), which provide additional targets for changes to gene-by-environment (or gene-by-gene) interactions. is large (Albert & Kruglyak, 2015;Yvert et al, 2003) and is often orders of magnitude larger than that of cis regulatory variants (Denver et al, 2005;Gruber, Vogel, Kalay, & WIttkopp, 2012;Landry, Lemos, Rifkin, Dickinson, & Hartl, 2007).…”
Section: Flexible Regulationmentioning
confidence: 99%
See 1 more Smart Citation